Panel 7: Otitis media: treatment and complications - Schilder AGM; Marom T; Bhutta MF; Casselbrant ML; Coates H; Gisselsson-Solén M; Hall AJ; Marchisio P; Ruohola A; Venekamp RP; Mandel EM (SAGE PUBLICATIONS LTD, 2025)
Objective. We aimed to summarize key articles published between 2011 and 2015 on the treatment of (recurrent) acute otitis media, otitis media with effusion, tympanostomy tube otorrhea, chronic suppurative otitis media and complications of otitis media, and their implications for clinical practice.
Data Sources. PubMed, Ovid Medline, the Cochrane Library, and Clinical Evidence (BMJ Publishing).
Review Methods. All types of articles related to otitis media treatment and complications between June 2011 and March 2015 were identified. A total of 1122 potential related articles were reviewed by the panel members; 118 relevant articles were ultimately included in this summary.
Conclusions. Recent literature and guidelines emphasize accurate diagnosis of acute otitis media and optimal management of ear pain. Watchful waiting is optional in mild to moderate acute otitis media; antibiotics do shorten symptoms and duration of middle ear effusion. The additive benefit of adenoidectomy to tympanostomy tubes in recurrent acute otitis media and otitis media with effusion is controversial and age dependent. Topical antibiotic is the treatment of choice in acute tube otorrhea. Symptomatic hearing loss due to persistent otitis media with effusion is best treated with tympanostomy tubes. Novel molecular and biomaterial treatments as adjuvants to surgical closure of eardrum perforations seem promising. There is insufficient evidence to support the use of complementary and alternative treatments.Implications for Practice. Emphasis on accurate diagnosis of otitis media, in its various forms, is important to reduce over-diagnosis, overtreatment, and antibiotic resistance. Children at risk for otitis media and its complications deserve special attention.